COVID-19 Revenue Administration Implications : Potential Tax Administration and Customs Measures to Respond to the Crisis - World Bank (World Bank, Washington, DC, 2020)
This note brings together the thinking that is occurring in global and regional teams on governance and institutional approaches to dealing with Coronavirus 2019 (COVID-19), with a focus on revenue administrations. It presents the governance and institutional reforms that can support revenue administration responses to COVID-19. The pandemic will bring a new normal where work practices should change. Usually, shocks trigger responses, and one of the responses here can be automatization of tax and customs services over the medium term, and a massive acceleration in the use of digital and virtual technologies.